Infection at an ecotone: cross‐system foraging increases satellite parasites but decreases core parasites in raccoons. Issue 9 (19th July 2019) - Weinstein, Sara B.; Van Wert, Jacey C.; Kinsella, Mike; Tkach, Vasyl V.; Lafferty, Kevin D.
Abstract: Ecotones can increase free‐living species richness, but little is known about how parasites respond to ecotones. Here, we use parasite communities in raccoons ( Procyon lotor ) to test the hypothesis that parasite communities can be divided into core and satellite species, each with fundamentally different responses to ecotones. We used published parasite surveys to classify parasites as common core or rare satellite species, and then surveyed raccoons in coastal California to examine how proximity to two aquatic ecotones altered parasite communities. Raccoons near ecotones had more satellite and fewer core parasite species. Specifically, the marine ecotone increased parasite diversity by adding satellite species to a persistent core community, whereas the freshwater ecotone shifted the community from core to satellite species without a net change in parasite richness. We hypothesize that increased parasite richness at the marine ecotone resulted from increased diet diversity, but that raccoons were sinks for some parasites. Increased exposure to rare parasites at ecotones has implications for wildlife health and provides insight into observed associations between ecotones and emerging disease.